Respiratory Failure Associated with the Lipodystrophy Syndrome in an HIV-Positive Patient with Compromised Lung Function - Natasha Press; Valentina Montessori; Tony R Bai; Julio Montaner (Canadian Respiratory Journal)
Protease inhibitors, used as treatment in human immunodeficiency virus (HIV) infection, are associated with a syndrome of peripheral lipodystrophy, central adiposity, hyperlipidemia and insulin resistance. An HIV-positive patient with chronic obstructive pulmonary disease is presented who developed the lipodystrophy syndrome that is associated with the use of protease inhibitors. It is postulated that the lipodystrophy syndrome further compromised his lung function, leading to respiratory failure. Patients who have pulmonary disease and are taking protease inhibitors require monitoring of clinical status and pulmonary function tests.